Effect of vegetation on snow cover at the northern timberline: a case study in Finnish Lapland - Vajda, Andrea; Venäläinen, Ari; Hänninen, Pekka; Sutinen, Raimo (Silva Fennica, 2006)
The presence of permanent snow cover for 200â220 days of the year has a determining role in the energy, hydrological and ecological processes at the climate-driven spruce (Picea abies) timberline in Lapland. Disturbances, such as forest fires or forest harvesting change the vegetation pattern and influence the spatial variation of snow cover. This variability in altered snow conditions (in subarctic Fennoscandia) is still poorly understood. We studied the influence of vegetation on the small-scale spatial variation of snow cover and wind climate in the Tuntsa area that was disturbed by a widespread forest fire in 1960. Radar was applied to measure snow thickness over two vegetation types, the spruce-dominant fire refuge and post-fire treeless tundra. Wind modelling was used to estimate the spatial variation of wind speed and direction. Due to the altered surface roughness and the increased wind velocity, snow drifting was more vigorous on the open tundra, resulting in a 30-cm thinner snow cover and almost half the water equivalent compared to the forest values. The changes in local climate after the fire, particularly in snow cover, may have played an important role in the poor recovery of vegetation: a substantial area is still unforested 40 years after the fire.